Drought alters the carbon footprint of trees in soils—tracking the spatio‐temporal fate of 13 C‐labelled assimilates in the soil of an old‐growth pine forest - Decai Gao; Jobin Joseph; Roland A Werner; Ivano Brunner; Alois Zürcher; Christian Hug; Ao Wang; Chunhong Zhao; Edith Bai; Katrin Meusburger; Arthur Gessler; Frank Hagedorn (Global Change Biology, 2021)
Above and belowground compartments in ecosystems are closely coupled on daily to annual timescales. In mature forests, this interlinkage and how it is impacted by drought is still poorly understood. Here, we pulse‐labelled 100‐year‐old trees with 13 CO 2 within a 15‐year‐long irrigation experiment in a naturally dry pine forest to quantify how drought regime affects the transfer and use of assimilates from trees to the rhizosphere and associated microbial communities. It took 4 days until new 13 C‐labelled assimilates were allocated to the rhizosphere. One year later, the 13 C signal of the 3‐h long pulse labelling was still detectable in stem and soil respiration, which provides evidence that parts of the assimilates are stored in trees before they are used for metabolic processes in the rhizosphere. Irrigation removing the natural water stress reduced the mean C residence time from canopy uptake until soil respiration from 89 to 40 days. Moreover, irrigation increased the amount of assimilates transferred to and respired in the soil within the first 10 days by 370%. A small precipitation event rewetting surface soils altered this pattern rapidly and reduced the effect size to +35%. Microbial biomass incorporated 46 ± 5% and 31 ± 7% of the C used in the rhizosphere in the dry control and irrigation treatment respectively. Mapping the spatial distribution of soil‐respired 13 CO 2 around the 10 pulse‐labelled trees showed that tree rhizospheres extended laterally 2.8 times beyond tree canopies, implying that there is a strong overlap of the rhizosphere among adjacent trees. Irrigation increased the rhizosphere area by 60%, which gives evidence of a long‐term acclimation of trees and their rhizosphere to the drought regime. The moisture‐sensitive transfer and use of C in the rhizosphere has consequences for C allocation within trees, soil microbial communities and soil carbon storage.

Binding of the D3-preferring antipsychotic candidate F17464 to dopamine D3 and D2 receptors: a PET study in healthy subjects with [11C]-(+)-PHNO - Mark Slifstein; Anissa Abi-Dargham; Ragy R Girgis; Raymond F Suckow; Thomas B Cooper; Chaitanya R Divgi; Pierre Sokoloff; Ludovic Leriche; Patrick Carberry; Shunichi Oya; Simon K Joseph; Marlène Guiraud; et al. (Psychopharmacology, 2020)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Use of a photoactivable GM1 ganglioside analogue to assess lipid distribution in caveolae bilayer - Marina Pitto; Joseph Brunner; Anita Ferraretto; Daniela Ravasi; Paola Palestini; Massimo Masserini (Glycoconjugate Journal, 2000)